CARBONATE AND SULFIDE ORE MINERALIZATION IN SEDIMENTS OF THE DERYUGIN RIFTOGENIC ZONE, SEA OF OKHOTSK - Astakhov A.S.; Kulinich R.G.; Kretser Y.L.; Tiedemann R. (My University, 2004)
In Cenozoic spreading zones of East Asian marginal seas, hydrothermal ore formation is known only in a few areas near volcanic arcs, such as the Okinawa Trough in the East China Sea. Subaeriall volcanism and hydrothermal activity related to convective cells are atypical of the majority of riftogenic troughs and depressions that are filled with thick terrigenous and biogenic-terrigenous sedimentary sequences. However, the thick sedimentary cover can generate abundant sedimentary (elisional) liquid and gaseous fluids in areas with intense heat flows. The fluids can migrate in sedimentary sequences and serve as a source of material. They can also govern specific hydrochemical conditions for the formation of different stratiform and massive sulfide ore deposits.